Pengaruh Gender, Pengetahuan Akuntansi, dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Berkarir Sebagai Akuntan Pemerintah - Arini; Zaharman; Serly Novianti (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to determine whether gender, accounting knowledge, and job market considerations influence students' interest in pursuing a career as a government accountant. The research approach used is quantitative with primary data sources. The population consists of students taking the Government Accounting course in the 2022/2023 and 2023/2024 in the Bachelor of Accounting Program at Lancang Kuning University, with a sample size of 56 students. Data analysis used multiple linear regression with SPSS 23 application. Statistical test results showed that gender did not significantly affect students' interest in pursuing a career as a government accountant, while accounting knowledge and job market considerations significantly affected students' interest in pursuing a career as a government accountant.